Pengurip : ARTS, CULTURE & FOOD OF THE TELANG USAN’S KAYAN - Awangko Hamdan, Awang Arshad; Sylvester Wielding, Jussem (Persatuan Wanita Kayan Telang Usan Miri (DOH KAYAN TELANG USAN MIRI) (DKTU), 2019)
The importance and preservation of knowledge of the Kayan community have gained increasing recognition. They are rich in the diversity and uniqueness of their language, customs, culture, and cuisine. Cultural objects such as beads, traditional bags, and tattoos as well as Kayan folk art and culture such as tekna', folk tales and local music, are among the lesser-known in modern society. Doh Kayan Telang Usan as an independent organization with a particular focus on the socio-economic and holistic development of Telang Usan Kayan women has strived to unite the arts, heritage, and culture as well as several traditional cuisines from 24 Kayan communities from Telang Usan, Baram, Miri, Sarawak. Through the collaboration with the Faculty of Applied and Creative Arts, Universiti Malaysia Sarawak, Doh Kayan Telang Usan has taken this initiative to document this knowledge and publish this book. Through the title of 'Pengurip' which means 'life' or 'way of life' in Telang Usan Kay an, this book can serve as a reference to the younger generation in getting to know the art, culture, and heritage of the Kayan people better.